MMC Pembentungan Langat Sdn. Bhd. / Umi Balkis Mohamed Hashim - Mohamed Hashim, Umi Balkis (Universiti Teknologi MARA, Sarawak, 2016)
MMC Corporation Berhad (MMC) is a leading utilities and infrastructure group with diversified businesses under three divisions, namely energy & utilities, ports & logistics and engineering & construction. Under the energy & utilities division, MMC has a controlling stake in Malakoff Corporation Berhad (Malaysia's largest independent power producer), is the single largest shareholder of Gas Malaysia Berhad (sole supplier of reticulated natural gas in Peninsular Malaysia to nonpower sector), and wholly owns Aliran Ihsan Resources Berhad (a water treatment plant operator). MMC's key businesses in its ports and logistics division include the operations of Port of Tanjung Pelepas (Malaysia's largest container terminal) and Johor Port (Malaysia's leading multi-purpose port). MMC also has a substantial shareholding in NCB Holdings Berhad which operates Northport in Port Klang and owns the largest container road haulage company in Malaysia. Through its associate stake in Red Sea Gateway Terminal Company Limited, MMC extends its operation in container port terminal in Jeddah Islamic Port in Saudi Arabia.